Strategic Value Networking for Market Entry: A study of the Russian retail market - Aldrete, Milton (My University, 2013)
In recent years the number of businesses eager to enter the Russian market has drastically increased triggered by the potential that the market has yet to offer. However due to limited international experience and notwithstanding the challenging nature of the targeted market many companies hesitate to establish operations. In existing literature there are various models of internationalization that illustrate the strategy and process of firms in their foreign market expansion but these models lack focus on complex and challenging economies where value networking plays an important role. For that reason the purpose of this study was to conduct a qualitative study to identify what the characteristics of strategic networking in Russia are for the successful establishment of operations and how firms with limited resources can generate value with key actors in the network. In order to do so, the research followed a qualitative study that analyzed eighth different cases of foreign retailers that have started operations in Russia with the purpose to use them real case examples. Moreover 14 experts representing different organizations were interviewed with the objective to obtain additional information and real experiences from actors currently involved in doing business in Russia. The main findings of this study provide an eye opening view of the importance of value networking in the establishments of operations in Russia as well as highlighting that this is an activity that can be challenging when differences in culture such as trust and perspective towards economic benefits come along. Thus this study provides comprehensive guidance for the identification of key actors and activities to enhance value creation in a network.
Keywords: Market Entry; Entry Modes; Russian Retail Market; Networking; Value Creation; Partner Selection.; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|